Free-H2 deoxygenation of Jatropha curcas oil into cleaner diesel-grade biofuel over coconut residue-derived activated carbon catalyst. (10th March 2020) - Asikin-Mijan, N.; Ooi, J.M.; AbdulKareem-Alsultan, G.; Lee, H.V.; Mastuli, M.S.; Mansir, Nasar; Alharthi, Fahad A.; Alghamdi, Abdulaziz Ali; Taufiq-Yap, Y.H.
Abstract: Diesel-like hydrocarbons were produced by the catalytic deoxygenation (DO) of Jatropha curcas oil (JCO) over novel Agx /AC and Niy -Agx /AC catalysts under an H2 -free atmosphere. The AC was synthesized from coconut fibre residues (CFR), where CFR is the by-product from coconut milk extraction and is particularly rich in soft fibres with high mineral content. The Niy -Agx /AC catalyst afforded higher DO activity via the decarboxylation/decarbonylation (deCOx) route than Agx /AC due to the properties of Ni, synergistic interaction of Ni and Ag species, adequate amount of strong acid sites and large number of weak acid sites, which cause extensive C-O cleavage and lead to rich formation of n -(C15 +C17 ) hydrocarbons. The effect of Ag and Ni content were studied within the 5 to 15 wt% range. An optimum Ni and Ag metal content (5 wt%) for deCOx reaction was observed. Excess Ni is not preferable due to a tendency for cracking and Ag-rich containing catalyst weakly enforced triglycerides breaking. The Ni5 -Ag5 /AC govern exclusively decarbonylation reaction, which corroborates the presence of Ni 2+ species and a high amount of strong acid sites. Ultimately, Ni5 -Ag5 /AC in the present study shows excellent chemical stability with consistent five reusability without drastic reduction of hydrocarbon yield (78–95%) and n -(C15 +C17 ) selectivity (82–83%), which indicate favourable application in JCO DO. Graphical abstract: Image 1 Highlights: Deoxygenation of Jatropha oil using Niy -Agx /AC catalysts. Ni metal promoted C-O bond cleavage. Abundancy of weak acid sites enhanced the deCOx pathways. High thermal stability of AC improves catalyst longevity.